Paradigm shift in the European Union’s space policy: institutional restructuring and its possible consequences for the CEE region - Bartóki-Gönczy, Balázs; Malinowska, Katarzyna (Frontiers in Political Science, 2025)
Developing capabilities in outer space has become crucial as the space segment becomes an increasingly important pillar of the economy and defence capabilities of states. Despite the growing global competition in and for outer space, in recent decades the EU and the ESA have focused their strategy on the civil aspects of space exploration. However, the crises emerging from Russia’s war on Ukraine has led the Member States to the conclusion that Europe must enhance its autonomous security and defence capabilities, especially in outer space. The main methods used in this study were the historical method and the legal analysis method. As a result of the crises, the EU has changed its politics recently adopted a space defence strategy, while it plans to propose an “EU Space Law Act” and is currently adapting its institutions to respond appropriately to the security challenges posed by the war on European territory and to the increasing competitiveness gap. First, the paper analyses the paradigm shift in the EU’s space policy and its implementation at the level of the institutions. Second, it will scrutinize the potential of the CEE region in connection with this paradigm shift. As a result of the crises, the EU has changed its politics recently adopted a space defence strategy, while it plans to propose an “EU Space Law Act” and is currently adapting its institutions to respond appropriately to the security challenges posed by the war on European territory and to the increasing competitiveness gap.